Models for Jewish Bible Theologies: Tasks and Challenges - Kalimi, Isaac (Horizons in biblical theology, 2017)
Against continuing attempts to define “Old Testament theology” or “biblical theology” in exclusively Christian terms, and in light of ongoing methodological diversity and confusion between proponents of Jewish biblical theology, this article suggests three models for the latter. The first one investigates the theologies of the different parts of the Hebrew Bible on their own, diachronically, without interference from later theology or practice. The second one focuses synchronically on the form of the Hebrew Bible as canonized, and is as objective as this basic biblical text allows. The third one is explicitly subjective and confessional, reading the Hebrew Bible in relation to the larger canon of Judaism, that is, the Oral Torah (= talmudic and midrashic literature). All three models have a legitimate place in the construction of a genuinely Jewish biblical theology, but they must not be confused. They all begin with different presuppositions and pursue different goals, but when properly distinguished, they can also complement one another, each exploring different aspects of the theology of the Jewish Bible.